Chosen Tax-Related and Economic Aspects of Choosing the Method of Equity Financing in Relation to Thin Capitalisation in the Countries of OECD - Dominik Gajewski (Contemporary Economics, 2012)
The present publication is concerned with the process of thin capitalisation in the countries of OECD. Two methods for financing companies are discerned in relation to this phenomenon, i.e. debt and equity financing. The tax-related consequences of the method of equity financing of companies are assessed against thin capitalisation. It is the very tax policy of companies that has a direct influence on the economic consequences of the functioning of these companies. The process of taxation of the phenomenon of thin capitalisation may be highly varied depending on the adopted method. Tax-related consequences demonstrate how complicated this process is irrespective of the country in which it takes place. The issue is even more complicated in the case of taxation of this process in companies conducting cross-border activity.